Berglund and McCullough on mastering Grails 101 - Berglund, Tim.; McCullough, Matthew; Safari eBooks ([S.l.] : O'Reilly, 2012)
"Grails is a high-productivity, convention-over-configuration web framework for the Groovy language. This brief video course begins with some basic instruction in the Groovy language, then shows you how to get started building a simple application using Grails domain modeling, controllers, and GSPs through the powerful scaffolding feature. In just three hours, you'll learn how to be productive with this exciting framework."--Resource description page.
Title, author names, and publisher from title screen.
Copyright date from end credits.
Presenters, Tim Berglund, Matthew McCullough .
Keywords: Grails (Computer file); Groovy (Computer program language); Web site development; Programming languages (Electronic computers); Application software -- Development; Open source software; Electronic books